A review of the current public health practice for contact tracing in relation to laryngeal TB in England 2012–2016. (May 2020) - Clarke, M.; Davidson, J.A.; Kar-Purkayastha, I.
Abstract: Objectives: Contact tracing following identification of tuberculosis (TB) is well established. However, evaluation of this activity, particularly for laryngeal TB, is limited. We compare contact tracing and outcomes in response to laryngeal TB with sputum-smear-positive pulmonary TB (ss + pTB) and consider the public health response in light of our findings. Study design: This study is a comparative secondary analysis of retrospective data, extracted from TB surveillance systems, to determine differences in contact tracing process and outcomes between two groups. Methods: Cases of laryngeal TB (without ss + pTB) notified in England between 2012 and 2016 were selected and matched to ss + pTB controls. Number of contacts identified and screened, along with screening outcomes were gathered from local databases. Results: There were 44 laryngeal TB cases who met inclusion criteria. The median number of contacts identified per case was 3 and 4 for controls ( P  = 0.04). Median number of contacts screened was 3 for cases and 4 for controls. The percentage of contacts with TB was 9.7 for cases and 20.3 for controls ( P  < 0.01). Conclusion: We observed a small difference, between case and control groups, in number of contacts identified but not number screened, indicative of a broadly similar approach to contact tracing. Conversely, the difference in screening outcomes between the groups was significant. These findings highlight a potential need to further understand infectivity of laryngeal TB; and consider possible implications for public health practice. Highlights: More contacts were identified for pulmonary compared to laryngeal TB cases. However, we found no difference in the number of contacts who underwent screening. This indicates that public health practice is similar for both forms of disease. mear +ve pTB contacts were twice as likely to have TB than laryngeal TB contacts.